3D‐Printed thermoplastic polyurethane/graphene composite with porous segregated structure: Toward ultralow percolation threshold and great strain sensitivity. Issue 14 (30th October 2020) - Mei, Shuxiang; Zhang, Xiaomeng; Ding, Bowen; Wang, Jiqiang; Yang, Pengfei; She, Haibo; Cui, Zhe; Liu, Minying; Pang, Xinchang; Fu, Peng
Abstract: Low‐percolation threshold and large deformation capacity are two critical attributes of the strain sensor, which determine its sensitivity and stability respectively. However, endowing these two attributes to the strain sensor simultaneously is still a great challenge in this field. In this work, the strain sensor with the three‐dimensional porous segregated structure constructed by graphene wrapped thermoplastic polyurethane (TPU) particles was fabricated successfully through the selective laser sintering technology. Results demonstrated that the percolation threshold of the composite is only 0.2 wt% and the strain gage factor can reach as high as 668.3, which represents the excellent sensitivity of the strain sensor. Furthermore, after 10 circles of stretching at the 15% strain, resistance‐strain behavior of the strain sensor shows great repeatable, which represents the remarkable stability. Therefore, the highly sensible and stable strain sensor was fabricated successfully, which will provide the guidance for the manufacture of the high‐performance strain sensor. Abstract :